Osteogenic potential of different chalcones in an in vivo model: A preliminary study. - Xana Raquel Ortolan; Telmo José Mezadri; David Rivero Tames; Rogério Corrêa; Fátima Campos-Buzzi (Universidad de Concepción., 2017)
Aim. To evaluate the osteogenic potential of chalcones using the rat critical size calvarial defect. Methods. The chalcones were synthesized from acetophenone following the Claisen-Schmidt aldol condensation method by varying the substituted benzaldehydes (3,4-Cl; 4-Cl; 4-CH3; 4-OCH3, H). The five chalcone molecules were evaluated in three concentrations (1%, 5% and 10%) in comparison to control and vehicle (Vaseline) groups. The results of the remaining wound areas were calculated statistically by the ANOVA method followed by the Student-Newman-Keuls test and the histological sections were analyzed qualitatively by light microscopy. Results. All molecules at 10% concentration showed significant bone closure compared to the control, vehicle and chalcone groups at 1% concentration (p<0.01). Active osteoblasts were observed on the repair surfaces in all groups treated with chalcones. Treatment with the C5 molecule at concentration of a 10% resulted in greater bone neoformation compared to the other molecules, with features of secondary bone observed. Conclusion. The chalcones evidenced a dose-dependent osteogenic potential and C5 was more effective in bone repair.